Beyond yield: plant disease in the context of ecosystem services - Cheatham, M. R.; Rouse, M. N.; Esker, P. D.; Ignacio, S.; Pradel, W.; Raymundo, R.; Sparks, Adam Henry; Forbes, G.A.; Gordon, T. R.; Garrett, Karen A. (My University, 2009)
The ecosystem services concept provides a means to define successful disease management more broadly, beyond short-term crop yield evaluations. Plant disease can affect ecosystem services directly, such as through removal of plants providing services, or indirectly through the effects of disease management activities, including pesticide applications, tillage, and other methods of plant removal. Increased plant biodiversity may reduce disease risk if susceptible host tissue becomes less common, or may increase risk if additional plant species are important in completing pathogen life cycles. Arthropod and microbial biodiversity may play similar roles. Distant ecosystems may provide a disservice as the setting for the evolution of pathogens that later invade a focal ecosystem, where plants have not evolved defenses. Conversely, distant ecosystems may provide a service as sources of genetic resources of great value to agriculture, including disease resistance genes. Good policies are needed to support conservation and optimal use of genetic resources, protect ecosystems from exotic pathogens, and limit the homogeneity of agricultural systems. Research is needed to provide policy makers, farmers, and consumers with the information required for evaluating trade-offs in the pursuit of the full range of ecosystem services desired from managed and native ecosystems.
Citation: Cheatham, M., . . . & Garrett, K. (2009). Beyond Yield: Plant Disease in the Context of Ecosystem Services. Phytopathology, 99(11), 1228-1236. https://doi.org/10.1094/PHYTO-99-11-1228
Keywords: Biological control; Ecosystem services; Plant disease